The Progressive HRM Paradigm: A Theoretical and Empirical Re-Examination - Godard, John (Relations industrielles / Industrial Relations, 1991)
This paper argues that the 'progressive paradigm ' — as it may be referred to — is at best oversimplified. It proceeds in three parts. Part one develops a critique of the two assumptions underlying this paradigm, arguingfirst that underlying sources of conflict inherent to work organizations and employment relations limit the effectiveness of progressive policies and practices, and, second, that the extent to which these policies and practices are economically rational and hence likely to be adopted varies in accordance with firm and industry-level structural variables. Following from this critique, part two draws upon a comprehensive set of survey data collected in 1980-81 from 100 unionized Canadian firms to explore both the effectiveness of, and structural variation in, progressive managerial practices. In part three,the implications of the analysis are briefly discussed.